ANALISIS SISTEM PENGAWASAN KUALITAS PRODUK PADA PT INDUSTRI SANDANG NUSANTARA UNIT PATAL SECANG DI MAGELANG JAWA TENGAH - Listiani Listiani (Jurnal Pendidikan Akuntansi Indonesia, 2006)
This research is aimed to determine the quality control system of production process in PT Industri Sandang Nusantara unit Patal Secang, measure the efectivity of quality control system by using control P-Chart and determine factors that cause defect product. This research is explorative descriptive by case study method. Data used in this research is the procedure of production process and the number of defect product. Product used in this company is  thread R30/1 UW and R 40/1 UW PT Industri Sandang Nusantara Unit Patal Secang in 24 periods of production between April – Mei 2006. Data is collected by interview, documentation, and observation. Data is analyzed by control p-chart and fish bone diagram. The conclusion of this research are: (1) The quality control system which is consists of controlling raw materials, production process and final product is appropriate with the company’s standard; (2) the number of defect product R 30/1 UW is 26.956 bale with the average 0.0167; Control P Chart shows that there are three periods which are out of control. They are in April 30, Mei 5 and 21, 2006. (3) The number of final product R 40/1 UW is 2159 bale with the average 0.0214; control p-chart shows that there are tw periods which are out of control. They are ini Mei 6 and Mei 12, 2006. (4) Factors that cause defect product are obsolete machines, employee performance, control system, and raw materials. Based on that condition, management should impove the controlling of machines, improve motivation and commitment of the employee, improve the method of inspection and control the quality of raw materials.